Problematik Definisi Harta Pailit untuk Mencapai Kepastian Hukum dalam Pelaksanaan Kepailitan dan PKPU - Tirayo, Adriel Michael; Halim, Yoefanca (Universitas Medan Area, 2019)
A legal product is expected to realize 3 legal purposes, which is Justice, Expediency and Legal Certainty. The definition of bankrupt assets is not mentioned implicitly in the Bankruptcy Law, that can lead to multiple interpretations. In practice, it happened in the court judgement Number 33/Pailit/2009/PN.Niaga.Jkt.Pst for the bankruptcy of PT. Tripanca Group, due to the absence of clear provisions relationg to bankruptcy assets. In this case, the problem to be answered is how is the implementation of bankrupt assets definitions in the court judgement Number 33/Pailit/2009/PN.Niaga.Jkt.Pst and the efforts that can be made related to the implementation of bankrupt assets definitions. This research used normative juridical method through literature study, then the data has been analized qualitatively and conclusions are drawn inductively. The results showed that the definition of